MicroRNA 143-145 deficiency impairs vascular function - Norata, Giuseppe; Pinna, C.; Zappella, F.; Elia, L.; Sala, A.; Condorelli, G.; Catapano, A. (2012)
MicroRNAs are required for vascular smooth muscle growth, differentiation and function. MiR143-145 modulates cytoskeletal dynamics and acquisition of the contractile phenotype by smooth muscle cells. Lack of this miRNA cluster results in decreased blood pressure and reduced vasocontraction. As all these observations point to a key role for miR143-145 in the vasculature, we investigated whether miR143-145 deficiency is associated with impaired vascular tone. Vasocontraction was assessed in isolated aortic rings from miR143-145 KO and wild type animals incubated with increasing concentrations of phenylephrine (10 -9 M to 10 -5 M) or KCI 0.3M. In both cases, aortic vessel contraction was dramatically reduced in miR143-145 KO animals compared to controls. Next, aortic rings were pre-contracted with phenylephrine (EC60: 10 -7 M) and concentration responses for acetylcholine were obtained. A significantly reduced vasodilation was observed in miR143-145 KO animals compared to controls and similar results were obtained when an exogenous donor of nitric oxide (sodium nitroprusside) was used. Endothelial nitric oxide synthase or guanylate cyclase mRNA expression were not different between the animal groups thus suggesting to investigate the effect of other vasodilators. Isoprenaline mediated vasodilation was significantly reduced in miR143-145 KO animals compared to controls in the absence or in the presence of the guanylate cyclase inhibitor ODQ (10 -4 M), suggesting that also beta adrenergic vasodilation is impaired following miR143-145 deficiency. Finally, the effect of a stable mimetic prostacyclin, namely iloprost, was investigated and again a reduced vasodilation was observed in miR143-145 KO animals. MiR143-145 deficiency is associated not only with altered vasocontraction but also with impaired vasodilation, which probably reflects the impaired VSMC differentiation phenotype reported in miR143-145 KO animals. Copyright © by BIOLIFE, s.a.s.